The effect of sulphates on anaerobic digestion of municipal wastewaters by using UASB reactors at 20 oC - Masood Abdusalam Ghanem Ali (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2019)
The aim of the work on sulphates was to investigate their impact on UASB performance, including the response to step changes in influent concentration. It has been shown that UASB reactors treating municipal-type wastewaters at 20 oC can remove sulphate effectively even at relatively low COD/SO4 ratios and/or high concentrations. In this experiment, therefore the UASB reactors were fed on influent with different sulphate concentrations to establish the effects on key performance parameters. It was used eight 4-litre continuously fed UASB reactors. The effect of sulphate addition on methane production was much greater than on COD removal, the specific methane production and the ratio of actual to theoretical methane produced per g of COD removed showed relatively little effect from influent sulphate concentrations below 120 mg SO4 l-1 (COD/SO4 ratio 5.8), although this may in part have reflected a period of acclimatisation while the population of sulphate-reducing bacteria (SRB) increased.